Genetic variability of brycon orbignyanus (valenciennes, 1850) (characiformes: characidae) in cultivated and natural populations of the upper paraná river, and implications for the conservation of the species - Panarari-Antunes,Renata de Souza (2011)
This study aimed to evaluate the genetic variability of B. orbignyanus in cultivated and natural populations of the Upper Paraná River, using molecular RAPD markers and mtDNA control region. Specimens were collected in the Paraná River and in the Piracema fish farm in Maringá, State of Paraná, Brazil. RAPD primers produced 82 loci with consistent expression. The population from the Paraná River showed 28 polymorphic loci, whereas the population from the fish farm presented only 12. Data revealed genetic differentiation between the two populations, although not very pronounced. These results were corroborated by the principal coordinate analysis and by neighbor-joining clustering. The alignment of the D-loop sequences of B. orbignyanus indicated the existence of polymorphism only in the natural population. These data could be helpful for the formulation of management strategies and conservation of the genetic diversity of the species.